EFFECT OF ANTI-MOLD AND MYCOTOXIN BINDER ON CORN QUALITY AND BROILER PERFORMANCE - Catootjie Lusje Nalle; Max A.J. Supit; Johanis A. Jermias; Damai Kusumaningrum; Melani Kefi; Ariska Benu (BIOTROPIA, 2025)
Article Highlights:- The anti-mold used effectively maintained low aflatoxin levels in 13% moisture corn.- Synthetic mold inhibitors effectively decreased aflatoxin levels in corn during storage and maintained some nutritional quality- Mycotoxin binder supplementation did not improve broiler- Broiler performance declined as aflatoxin concentrations increased Abstract: The quality of animal feed is determined by high-quality ingredients and appropriate feed additives. This study aimed to assess: 1) the nutrient and aflatoxin total (AT) content of corn treated with an anti-mold (A) and 2) broiler performance fed with aflatoxin B1 (AFB1)-contaminated diets supplemented with a mycotoxin binder (MB).  Two experiments were carried out to achieve the objectives. Experiment 1 was set up with a 2 x 2 Factorial Completely Randomized Design (FCRD) with two factors: moisture content (MC at 13 and 15%) and anti-mold (A, -/+). Meanwhile, Experiment 2 was set up with a  3 x 2 Factorial Completely Randomized Design with two factors: the AFB1 (< 100, 165, 222 µg/kg) and MB (-/ +). The MC and A interaction was significant (P < 0.01) on the aflatoxin total of corn throughout the 2-month assay. The utilization of the anti-mold in afla-corn with different moisture levels did not influence (P > 0.05) corn’s nutrient content. The MC x A interaction was significant (P < 0.05) in the valine and glycine content of the stored corn. In the second experiment, no interaction of AFB1 x MB (P > 0.05) was observed in the bird’s performance during the study. The AFB1 Concentration (AC) of corn decreased significantly (P < 0.05 to 0.001) in feed intake, body weight gain, and feed efficiency of birds. Our study concluded that the anti-mold effectively maintained low aflatoxin levels in 13% moisture corn. Also, the anti-mold did not affect the nutrient profile of corn during storage. Our study also showed that mycotoxin binder supplementation did not improve broiler performance and broiler performance declined as aflatoxin concentrations increased.